Ennis Franciscan Friary, tomb niche under tower, capital - O'Donovan, Danielle (My University, 2008)
Sketch of capital of tomb niche jamb, moulding from top down comprises: abacus, chamfer, scroll, hollow chamfer, bell, necking roll. One of a number of Flamboyant tombs found on or west of the Shannon. The Ennis example is closest in design to that in the north chancel wall at Athenry Dominican Friary.
Tomb niche
Keywords: scroll; Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Gothic capitals (Architecture); Late Medieval; roll moldings; moldings, hollow